Analyzing Short-Run and Long-Run Causality between FDI Inflows, Labor Productivity and Education in Pakistan - Serfraz, Ayesha (Asian Journal of Economics and Empirical Research, 2018)
This study empirically analyzes the causal relationship between FDI inflows, labor productivity and education in case of Pakistan using time series data from 1971-2016. The present study concentrates only on labor productivity since Pakistan is a labor abundant country where provision of education is solely the responsibility of Government of Pakistan. For empirical analysis, it uses the latest test for measuring causality i.e., Breitung-Candelon Granger Causality test in frequency domain (both old and new versions). The traditional approach of Johansen Cointegration test has also been applied to check robustness of results. Both versions of BC test, i.e., Breitung and Candelon (2006) and Breitung and Schreiber (2016) suggest a univariate causality running from FDI to labor productivity only, whereas Johansen Cointegration approach suggests a long run relationship among three variables. Therefore government of Pakistan must give proper attention to education sector in order to gain maximum benefits from FDI inflows.